Desain Struktur Gaji, Kepesertaan Bpjs Tenaga Kerja, Jemaat Surya Kasih Pondok Kopi Jakarta Timur - Anton PW Nomleni; Leo Alexander Tambunan; Yortan Kusa; Fadia Ayu Ningrum; Morris Sidauruk (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2024)
The secretariat office has employees including the head of the office, cashier, security guard and boarding house, and the management of this office is under the super- vision of the Chair of the 5 Daily Management of the Congregation Council (PHMJ). GPIB office employees of the Surya Kasih Congregation receive salaries provided by the Surya Kasih Congregation for employees with local status and by the synod if the status is as a synod employee. So far, salaries have been given in the form of a single unit with- out a salary structure that is in accordance with church regulations, where there are ele- ments of allowances and determination of their amounts. Then every employee has been registered to participate in BPJS labor, but it is limited to "work accident insurance (JKK)" and "death guarantee (JKM)" while those that have not been followed are "pen- sion guarantee (JP)" and "old age guarantee (JHT). )”. Apart from that, to be able to pro- vide a salary value and benefits, it must be based on an objective and structured work per- formance assessment, then involve employees, their leaders and then a provision will be made as a permanent employee. Based on this, it has been registered to take part in "pen- sion guarantee (JP)" and "old age guarantee (JHT)". Then previously there was no in- strument for assessing employee performance objectively, so a form of performance as- sessment with several indicators was also prepared.